Clinical importance of anatomical variants of sciatic nerve in relation to the piriformis muscle - Rashmi Deopujari; Dibya Kishore Satpathi; Ashutosh S Mangalgiri (Wolters Kluwer Medknow Publications, 2012)
Background and aims: The sciatic nerve usually emerges below the Piriformis muscle. Each anatomical variant of sciatic nerve is associated with a specific clinical presentation. The aim of the study was to identify the variants of sciatic nerve and to discuss their clinical importance. Materials and methods: Twenty one embalmed cadavers of known age and sex were used for this study. Gluteal regions of both sides were dissected to expose sciatic nerve. Variation of sciatic nerve in relation to piriformis was observed. Results and Conclusion: Out of the 42 dissected specimens - Five showed variations in sciatic nerve. Three specimens (two on right and one on left side) displayed common peroneal branch passing through piriformis. Three specimens (two on right and one on left side) showed tibial nerve emerging below piriformis.In one specimen on left side common peroneal nerve emerged as two parts in relation to piriformis - one passing through piriformis and another below piriformis. Avery unusual variant in which the tibial and common peroneal components of sciatic nerve were sandwiched between the three heads of piriformis muscle is also reported here in one case of right side. These variants are usually misdiagnosed in most of the cases due to similarity of clinical symptoms with low back ache and sciatica. Therefore the possibility of each such variant should be kept in mind by the clinicians.